Ozone Fumigation on Sulfur Dioxide Treated Longan for Sulfur Residue Reduction and Delaying of Pericarp Browning as well as Disease Control in Longan Fruit during Storage - Taimaneerak, Aunchalee; Uthaibutra, Jamnong; Sugaya, Sumiko; Kunkhum, Warapan; Whangchai, Kanda (Food and Applied Bioscience Journal, 2018)
Effect of ozone fumigation on sulfur residue reduction and postharvest qualities of sulfur dioxide treated longan fruit was investigated. The longans which were sulfur dioxide fumigated were divided into two groups. In the first group, the fruits were exposed to ozone gas (O3) at a concentration of 200 ppm for 10 h, while the fruits of the second group were placed at room temperature as the control. The two groups of the longan fruit were randomly selected for 0 h, 2 h, 4 h, 6 h, 8 h and 10 h to determine the sulfur residue in the pericarp and the aril. The result showed that the sulfur residue was reduced by 93.50% in the pericarp and 81.54% in the aril after 10 h of ozone exposure. In the second experiment, the effect of ozone on disease incidence and pericarp browning of sulfur dioxide treated longan fruit was investigated. The results showed that all the treated fruits had lower browning index and PPO activity than the control group. None of the longans treated with ozone showed disease incidence or presence of microorganism population immediately after fumigation and for 5 days in storage at 25°C. Moreover, the ozone treatment also delayed the changes that take place in the postharvest qualities of SO2-treated longan fruit after storage at 5°C for 35 days. It was concluded that ozonation is an alternative method for reducing sulfur residue, controlling disease incidence, and maintaining postharvest quality of SO2-treated longan fruit.